Carbon Quantum Dots–Modified Interfacial Interactions and Ion Conductivity for Enhanced High Current Density Performance in Lithium–Sulfur Batteries. Issue 7 (21st December 2018) - Hu, Yin; Chen, Wei; Lei, Tianyu; Zhou, Bin; Jiao, Yu; Yan, Yichao; Du, Xinchuan; Huang, Jianwen; Wu, Chunyang; Wang, Xuepeng; Wang, Yang; Chen, Bo; et al.
Abstract: Significant progress has achieved for developing lithium–sulfur (Li–S) batteries with high specific capacities and excellent cyclic stability. However, some critical issues emerge when attempts are made to raise the areal sulfur loading and increase the operation current density to meet the standards for various industrial applications. In this work, polyethylenimine‐functionalized carbon dots (PEI‐CDots) are designed and prepared for enhancing performance of the Li–S batteries with high sulfur loadings and operation under high current density situations. Strong chemical binding effects towards polysulfides and fast ion transport property are achieved in the PEI‐CDots‐modified cathodes. At a high current density of 8 mA cm −2, the PEI‐CDots‐modified Li–S battery delivers a reversible areal capacity of 3.3 mAh cm −2 with only 0.07% capacity decay per cycle over 400 cycles at 6.6 mg sulfur loading. Detailed analysis, involving electrochemical impedance spectroscopy, cyclic voltammetry, and density functional theory calculations, is done for the elucidation of the underlying enhancement mechanism by the PEI‐CDots. The strongly localized sulfur species and the promoted Li + ion conductivity at the cathode–electrolyte interface are revealed to enable high‐performance Li–S batteries with high sulfur loading and large operational current. Abstract : A new type of carbon quantum dots–modified cathode named PEI‐CDots@AB/S for lithium–sulfur ( Li–S) batteries is synthesized and reported, which enables the achievement of a real capacity of 3.3 mAh cm −2 with only 0.07% capacity decay per cycle over 400 cycles at the current density of 8 mA cm −2, leading to a significant performance improvement in Li–S batteries.